Brain structural abnormalities in behavior therapy-resistant obsessive-compulsive disorder revealed by voxel-based morphometry - Hashimoto, Nobuhiko (Dove Medical Press, 2014)
BACKGROUND: Although several functional imaging studies have demonstrated that behavior therapy (BT) modifies the neural circuits involved in the pathogenesis of obsessive-compulsive disorder (OCD), the structural abnormalities underlying BT-resistant OCD remain unknown. METHODS: In this study, we examined the existence of regional structural abnormalities in both the gray matter and the white matter of patients with OCD at baseline using voxel-based morphometry in responders (n=24) and nonresponders (n=15) to subsequent BT. Three-dimensional T1-weighted magnetic resonance imaging was performed before the completion of 12 weeks of BT. RESULTS: Relative to the responders, the nonresponders exhibited significantly smaller gray matter volumes in the right ventromedial prefrontal cortex, the right orbitofrontal cortex, the right precentral gyrus, and the left anterior cingulate cortex. In addition, relative to the responders, the nonresponders exhibited significantly smaller white matter volumes in the left cingulate bundle and the left superior frontal white matter. CONCLUSION: These results suggest that the brain structures in several areas, including the orbitofrontal cortex, anterior cingulate cortex, and cingulate bundles, are related to the lack of a response to BT in patients with OCD. The use of a voxel-based morphometry approach may be advantageous to understanding differences in brain abnormalities between responders and nonresponders to BT.